Students Difficulties in Using Simple Past Tense in Narrative Text at Tenth Grade of Senior High School 8 Muaro Jambi - Suyadi, Suyadi; Silfia, Efa; Nurhasanah, Riska Meilina (Universitas Batanghari Jambi, 2024)
This research aims to find out the levels of difficulty faced by tenth-grade students at Senior High School 8 Muaro Jambi in using simple past tense within narrative texts. The research used a quantitative descriptive research design with purposive sampling. 28 students from class XE 4 were taken as participants. The researcher used a test as an instrument. The findings reveal that the students fall into 4 categories: Very Poor, Poor, Moderate, and Good levels. 13 students in the